he Stone Age site and paleontological location near the village of Comintern (at the confluence of the Kama and Volga): research results 2020 - Galimova Madina Sh.; Berezin Alexander Yu.; Berezina Natalia S.; Mikhailov Evgeny P. (Археология евразийских степей, 2021)
The paper features the results of archaeological and paleontological research in the left bank of the Kuibyshev reservoir, at the mouth of the Aktai River (Republic of Tatarstan). Bones and teeth of fossil mammals (223 finds) were collected under the cliff of the reservoir for 300 m. The following species were identified: mammoth, woolly rhinoceros, bison, tur, horse, reindeer, elk, fox, marmot etc., which may belong to the Upper Pleistocene or Khazar faunal complexes. Also the bones of the limb of a large horse were collected, which were identified as a horse of Mosbach of the middle Neo-Pleistocene Singil’ faunal complex existed in the Volga region about 400 thousand years ago. Upper incisor of a giant beaver and the large jaws of a Pleistocene wild boar were also found at the Comintern site and were probably attribute to Singil’ fauna. At the same time, the authors collected 39 artifacts from flint and one from quartzite, belonging to the Ust’-Kamaskaya culture of the terminal Paleolithic. Of particular importance were two localities fixed by the authors in stratified sections – flint flake and rhinoceros limb bone, which lay within the buried soil formed during the warming period of the Middle Valdai (MIS-3).